Screening of MSI detection loci and their heterogeneity in East Asian colorectal cancer patients. (3rd April 2019) - Bai, Wenqi; Ma, Jinfeng; Liu, Yangyang; Liang, Jing; Wu, Yueqin; Yang, Xuanqin; Xu, Enwei; Li, Yan; Xi, Yanfeng
Abstract: Objective: This study aims to screen the MSI detection loci suitable for the East Asian colorectal cancer patients. and explore its intratumoral heterogeneity. Methods: A total of 271 pathological tissues specimens of colorectal cancer were collected. The MSI status was detected using different PCR reagent kits with different detection loci. Then, the results were compared with the immunohistochemical (IHC) staining results. Microdissection of pathological tissues specimens detected to be MSI‐H was performed to examine whether there was intratumoral heterogeneity of MSI status. Results: Thirty‐nine out of 271 cases were dMMR. dMMR occurred mostly in patients with right‐hemi colon cancer ( P < 0.0001). Compared with dMMR patients, the clinical stages of pMMR patients were more inclined to be in the late stage with lymph node metastasis ( P < 0.0001). MSI‐H tumors were significantly associated with KRAS mutation ( P = 0.036) and PD‐L1 expression ( P = 0.038). Compared with Promega panel and 24‐locus detection, the consistency between NCI MSI panel and IHC staining results were the highest with the Kappa value of 0.850. The sensitivity of detection decreased from 87.18% to 56.41% with the increase in detection loci. Single locus analysis showed that the first two loci with the highest sensitivity were both mononucleotide loci, namely, BAT‐26 (95.45%) and BAT‐25 (86.36%). The dinucleotide locus with highest sensitivity was D2S123 (50%). The main detection loci of MSI‐H showed no intratumoral heterogeneity. Conclusion: The combination of 2 mononucleotide loci (BAT25, BAT26) and 3 dinucleotide loci (D2S123, D5S346, D17S250) might be the most suitable loci for MSI detection in East Asian population. There is no intratumoral heterogeneity in the main MSI loci. Abstract : Our study focuses on the screening of MSI loci in Chinese colorectal cancer patients for the first time. The combination of 2 mononucleotide loci (BAT-25 and BAT-26) and 3 dinucleotide loci (D2S123, D5S346, and D17S250) might be the most suitable for MSI detection in Chinese population.